Intermediate Products of C60 High‐Temperature Chlorination – C60Cln (n = 8, 10, 14, 20, 24). Issue 43 (20th October 2020) - Tamm, Nadezhda B.; Markov, Vitaliy Yu.; Goryunkov, Alexey A.; Troyanov, Sergey I.
Abstract : The products of high‐temperature (440 °C) chlorination of C60 with SbCl5 differ considerably from the products obtained at room temperature because high‐temperature allows for chlorine migration over the fullerene cage. Thus, one can expect to obtain the most favorable chlorination patterns for any C60 Cl n stoichiometry. We report the isolation and structural characterization of several chlorofullerenes, C 2 v ‐C60 Cl8, C 1 ‐C60 Cl10, and C 1 ‐C60 Cl14, which are intermediates to the more kinetically stable higher chlorides. Theoretical DFT calculations of formation energies verified the high thermodynamic stability of the isolated chlorides. Further chlorination produces T h ‐C60 Cl24 and, eventually, non‐IPR chlorides, 1805 C60 Cl24 and 1794 C60 Cl20 . as a result of cage rearrangements. Also isolated is a product of the cage shrinkage, C58 Cl20 . Abstract : High‐temperature chlorination of C60 with SbCl5 enables chlorine migration and thus leads to the most favorable chlorination patterns that can differ from the room‐temperature ones. We report the isolation and characterization of several IPR chlorofullerenes of intermediate stoichiometry: C60 Cl8, C60 Cl10, C60 Cl14, and C60 Cl24, together with the non‐IPR 1805 C60 Cl24 and 1794 C60 Cl20, and a product of fullerene cage shrinkage, C58 Cl20 .